(3bdGFO GdYbjGf heMGSf GdCYjGfs - (3CHi fUQ GdaJM Hf eMeO Hf YHjO Gddg Hf NGbGf GdbjSi GdETHjdi,J (B528 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QGVi dfG GdHjGf MJi GfbGO ai CYfJfG hHYO aEf GdCOH CLed eG GdJMaJg GdgeI hYQaJg gPg GdCeI s
(3BNQgG (B:s
(3hQaV cJGH Gddg GdYdje GdMcje hjegd MceI ef Gddg hYdeG h(B( (3EfeG Zdi dge djROGOhG EKeGk (B) (3hUdi Gddg s
(3HgG CKGQ JbWjY hJQbjY hWeSs
(3LeY ajg WGFaI ef TYQGA GdeZQH hGdCfOdS hChQO JQGLege hCNHGQge hWQakG ef GTYGQges
(3GdeYgO fSN CNQi HQeb (B385 (3, (B1175 (3, (B1898 (3JGQjNs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B49s
Keywords: (3GdJGQjNs